Fat oxidation rates in professional football players - Randell, R. K.; Rollo, I.; Medina, D.; Lizarraga, M. A.; Jeukendrup, A. E.; Carter, J. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The rates of maximal fat oxidation (MFO) and the exercise intensity at which it occurs (FATMAX), has been reported in obese, sedentary, lean and endurance trained populations. To date there are no data available describing fat oxidation rates in professional football players. Methods: During pre-season medical testing (2014 - 2015 season) 28 players (age 24 ± 4 y; body mass 74.3 ± 6.1 kg; stature 178.8 ± 7.0 cm; body fat 13.8 ± 2.6 %) from the professional football team at FC Barcelona completed a FATMAX test. Performed in a fasted state (> 5 h) on a treadmill, the test started at 5 km/h at a gradient of 1% for 3 min. The speed increased to 8 km/h and, thereafter, increased by 2 km/h until a respiratory exchange ratio (RER) of 1 was reached. The speed then remained constant and the gradient was increased by 1% every 1 min to determine peak oxygen uptake (VO2peak). Respiratory gas measurements (VO2 and VCO2) and heart rate (HR) were measured continuously. Stoichiometric equations [1] were used to calculated fat oxidation rates during each 3 min stage of the test to determine MFO. Heart rate max (HRmax) and VO2peak were measured in order to calculate FATMAX. Results: The average MFO of professional football players was 0.75 g min-1 ± 0.18. The lowest absolute MFO rate was 0.45 g min-1, whereas the highest MFO measured was 1.18 g min-1. FATMAX occurred at an average exercise intensity of 51 ± 7% VO2peak (range 27 - 60% VO2peak), equating to 66% ± 5 of maximal HR (range 56 - 77% maximal HR). Conclusion: Our results show that, on average, professional football players have a high capacity to oxidise fat during exercise. However, there is a wide range in MFO and the exercise intensity at which it occurs, potentially emphasizing the importance of personalized nutrition strategies. Further investigation is required to determine the importance and the implications of accounting for substrate oxidation rates, and their interaction with exercise intensity, with regard to football specific training, performance and nutrition recommendations. ABSTRACT FROM AUTHOR